2007
DOI: 10.1002/ijc.23214
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric factors and risk of melanoma in women: A pooled analysis

Abstract: Anthropometric factors such as height, weight and body mass index are related to the occurrence of certain malignancies in women including cancers of the breast, ovary and endometrium. Several studies have investigated the relation between height and weight or body mass and the risk of cutaneous melanoma in women, but results have been inconsistent. We conducted a collaborative analysis of these factors using the original data from 8 case-control studies of melanoma in women (2,083 cases and 2,782 controls), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 59 publications
(103 reference statements)
1
41
1
6
Order By: Relevance
“…However, in agreement with our results, the lack of analyses adjusting BSA for height could result in incorrect identification of BSA as an MM risk factor, even though it is in fact the height parameter of BSA that is the main driver of the positive association with MM risk. In regard to the BMI-MM association, results of previous studies contradict each other (1216, 21, 28, 30), making it difficult to disentangle whether BMI is a risk factor for melanomagenesis. Nevertheless, sex-specific differences have been reported, with BMI being significantly associated with MM development in men but not in women, conceivably resulting from different sunbathing habits in obese women (12).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, in agreement with our results, the lack of analyses adjusting BSA for height could result in incorrect identification of BSA as an MM risk factor, even though it is in fact the height parameter of BSA that is the main driver of the positive association with MM risk. In regard to the BMI-MM association, results of previous studies contradict each other (1216, 21, 28, 30), making it difficult to disentangle whether BMI is a risk factor for melanomagenesis. Nevertheless, sex-specific differences have been reported, with BMI being significantly associated with MM development in men but not in women, conceivably resulting from different sunbathing habits in obese women (12).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have found associations between greater adult height and MM (12, 13, 1620), and generally height displays the strongest association with MM as compared with cancers at other anatomical sites (1720). Similarly, although there are discrepancies in the literature (1216, 28, 29), BSA is generally positively associated with MM development. However, in agreement with our results, the lack of analyses adjusting BSA for height could result in incorrect identification of BSA as an MM risk factor, even though it is in fact the height parameter of BSA that is the main driver of the positive association with MM risk.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this association are increased skin surface or higher naevi count in taller individuals, or differences in distribution of other risk factors such as sun exposure [30]. However, adjusting for physical appearance and sun exposure-related factors associated with risk of melanoma did not affect the risk estimates for height and risk in one pooled analysis of 2,083 female cases of malignant melanoma [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Adult height, determined by genetics and by nutrition in childhood, has been associated with an increased risk of some cancers such as cancer of the prostate [1], breast [2], colorectum [3], ovary [4, 5], pancreas [6], kidney [7], testis [8], endometrium [9], malignant melanoma [2, 10, 11], and with lymphohematopoietic malignancies [12]. However, there are only a few studies on all cancer sites, [2, 1315] and only one of these studies included men as well as women [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, evidence from epidemiologic research regarding the association between BMI and NMSC combined or only BCC is mixed, with several studies finding an inverse relationship [13-18], and other studies being null [19-22]. Some studies of melanoma [12, 21, 23] and one of BCC [21] have also investigated body surface area (BSA) as an alternate anthropometric measure, with results generally mirroring the BMI findings in each population.…”
Section: 1 Introductionmentioning
confidence: 99%